2022
DOI: 10.47391/jpma.1443
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, screening, Practices and attitudes of cervical cancer among doctors and nursing staff working at a tertiary care center

Abstract: Objectives: To assess knowledge, attitude and practice of medical and paramedical staff about cervical cancer as well as its screening and prevention. Methods: The descriptive cross-sectional study was conducted at the Jinnah Post-graduate Medical Centre, Karachi, from March 1 to August 30, 2019, and comprised women medical and paramedical staff randomly selected from different specialties. Data was collected using a structured questionnaire. Data was analysed using SPSS 20. Results: Of the 347 participants 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
0
1
Order By: Relevance
“…The knowledge of VIA was less than Pap test, which could be alarming as VIA is a technique that is primarily targeted to be conducted by the nursing staff for cervical cancer screening in low-resource areas. In our study, 92.8% were aware of the Pap test as a screening method, compared to 68.9% in a similar study conducted in Pakistan [14]. However, awareness of VIA as a recall question was 12.4% at the start of the study, but with further succession of the study, with prior priming effect, 70.8% of participants were able to identify VIA as a screening method for cervical cancer.…”
Section: Discussioncontrasting
confidence: 76%
“…The knowledge of VIA was less than Pap test, which could be alarming as VIA is a technique that is primarily targeted to be conducted by the nursing staff for cervical cancer screening in low-resource areas. In our study, 92.8% were aware of the Pap test as a screening method, compared to 68.9% in a similar study conducted in Pakistan [14]. However, awareness of VIA as a recall question was 12.4% at the start of the study, but with further succession of the study, with prior priming effect, 70.8% of participants were able to identify VIA as a screening method for cervical cancer.…”
Section: Discussioncontrasting
confidence: 76%
“…The study was observed (32.6%) single para-medical staff, the percentage (65.4%) were married and (2% widow and divorced), in comparison with other reported studies this result was similar with other reported study done by [13] in Central Ethiopia who found the higher percentage (61.4%) was married. But disagree with the study result done in Iran by [14] and in Pakistan by [15] which shows that most of study participant were single (81.5%), (68%) respectively. this difference may be due to that the study was conducted in Pakistan was on students who were younger than 24 years old, so the majority of the sample was unmarried, while the current study was on health workers and their ages ranged between 22 to 63 years, so the higher percentage of them were married.…”
Section: Discussioncontrasting
confidence: 67%
“…The frequency of cervical cancer screening uptake by HCWs varies among countries, eg, Pakistan (17.6%), Jordan (19.1%), Saudi Arabia (26.2%), Turkey (4.2-45.2%), Qatar (42.2%), and Taiwan (70.6%). 14,[25][26][27][28][29][30][31] Differences in cultural background and demographic characteristics of participants, the risk factor profile and epidemiology of cervical cancer, the healthcare system, and methodologies could contribute to these differences.…”
Section: Discussionmentioning
confidence: 99%